"Turn-On" monopodal and dipodal nanoprobes for serum albumins – a case of shift in selectivity towards BSA and a Z- to U-like conformational change. (23rd August 2022) - Dhiman, Sukhvinder; Kour, Rasdeep; Kumar, Gulshan; Kaur, Satwinderjeet; Luxami, Vijay; Singh, Prabhpreet; Kumar, Subodh
Abstract : The flexibility in dipodal DPDM results in its contrasting behavior towards serum albumins in comparison to monopodal MPMB . Abstract : The present study provides an insight into the difference in binding of monopodal (MPMB ) and dipodal (DPDM ) fluorescent probes in the cavity of serum albumins (SAs). The aggregates of DPDM show nearly 4-fold preference towards BSA (66-fold enhancement) over HSA (17-fold enhancement) in fluorescence intensity but aggregates of MPMB exhibit a similar response towards BSA, HSA and RNA. DPDM and MPMB do not show fluorescence responses to other proteins and biomolecules. The mechanism of interaction of these probes with SAs has been investigated through drug binding, fluorescence lifetime, fluorescence anisotropy, FT-IR, DLS, circular dichroism and docking studies. The docking and drug binding studies in consonance with each other show that MPMB preferably binds at the bilirubin site (subdomain IB) of BSA but DPDM undergoes a Z- to U-like conformation change during binding in the cavity of BSA and binds near to both the bilirubin and ibuprofen sites. The increase in lifetime of both DPDM and MPMB in the presence of BSA/HSA points to a dynamic mechanism of interaction. Probe DPDM detects as low as 14 nM BSA and 141 nM HSA but in the case of MPMB, the detection limits are 90 nM BSA and 30 nM HSA. The decrease in size of aggregates of DPDM from 34 nm to 6 nm in the presence of BSA (DLS) confirms the complexation of DPDM in its cavity.